A prospective study of surgical site infections in a tertiary care hospital - Reddy Chada, Chenna Krishna; Kandati, Jithendra; Ponugoti, Munilakshmi (International Surgery Journal, 2017)
Background: Among the Health care associated infections (HAI), surgical site infections (SSI) previously termed as post-operative wound infections are one of the most common HAI in low and middle income countries. Increase in SSI is associated with increased morbidity, as well as mortality due to emergence of antimicrobial resistant pathogens. Understanding the pathogens implicated in causing the SSIs and their antimicrobial sensitivity place a good role in reducing the mortality and morbidity. Methods: A prospective study was conducted at a tertiary care hospital to all the patients admitted in Department of surgery, Orthopedics and Gynecology and Obstetrics for six months from January 2016 to June 2016. The demographic data, inclusion criteria and exclusion criteria, risk factors, clinical history, laboratory data with gram stain, culture results and antibiotic sensitivity of the isolates were collected. Results: Two hundred patients were recruited in the study and the prevalence of SSI in the study was 3.83%. Patients who underwent emergency operations and diabetics were at higher risk of acquiring SSI. The most commonly isolated pathogens in the study were Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Pseudomonas aeruginosa was most common isolate from orthopedic cases of SSI, Escherichia coli was most common isolate from intestinal surgeries and Staphylococcus aureus from LSCS. Increased rate of isolation of MRSA and ESBL strains were observed in the study. Conclusions: Study clearly explains the various causes and risk factors associated in development of SSI. The study guides in the type of the organism isolated and possible antibiotic of choice in treatment and management of SSI. The prevalence of SSI was 3.83%, which is comparable with some of the studies and lower than many of the studies.